Emerging phenotypes linked to variants in SAMD9 and MIRAGE syndrome - Suntharalingham, Jenifer P.; Ishida, Miho; Del Valle, Ignacio; Stalman, Susanne E.; Solanky, Nita; Wakeling, Emma; Moore, Gudrun E.; Achermann, John C.; Buonocore, Federica (Frontiers in Endocrinology, 2022)
Background Heterozygous de novo variants in SAMD9 cause MIRAGE syndrome, a complex multisystem disorder involving Myelodysplasia, Infection, Restriction of growth, Adrenal hypoplasia, Genital phenotypes, and Enteropathy. The range of additional clinical associations is expanding and includes disrupted placental development, poor post-natal growth and endocrine features. Increasingly, milder phenotypic features such as hypospadias in small for gestational age (SGA) boys and normal adrenal function are reported. Some children present with isolated myelodysplastic syndrome (MDS/monosomy 7) without MIRAGE features. Objective We aimed to investigate: 1) the range of reported SAMD9 variants, clinical features, and possible genotype-phenotype correlations; 2) whether SAMD9 disruption affects placental function and leads to pregnancy loss/recurrent miscarriage (RM); 3) and if pathogenic variants are associated with isolated fetal growth restriction (FGR). Methods Published data were analyzed, particularly reviewing position/type of variant, pregnancy, growth data, and associated endocrine features. Genetic analysis of SAMD9 was performed in products of conception (POC, n=26), RM couples, (couples n=48; individuals n=96), children with FGR (n=44), SGA (n=20), and clinical Silver-Russell Syndrome (SRS, n=8), (total n=194). Results To date, SAMD9 variants are reported in 116 individuals [MDS/monosomy 7, 64 (55.2%); MIRAGE, 52 (44.8%)]. Children with MIRAGE features are increasingly reported without an adrenal phenotype (11/52, 21.2%). Infants without adrenal dysfunction were heavier at birth (median 1515 g versus 1020 g; P < 0.05) and born later (median 34.5 weeks versus 31.0; P < 0.05) compared to those with adrenal insufficiency. In MIRAGE patients, hypospadias is a common feature. Additional endocrinopathies include hypothyroidism, hypo- and hyper-glycemia, short stature and panhypopituitarism. Despite this increasing range of phenotypes, genetic analysis did not reveal any likely pathogenic variants/enrichment of specific variants in SAMD9 in the pregnancy loss/growth restriction cohorts studied. Conclusion MIRAGE syndrome is more phenotypically diverse than originally reported and includes growth restriction and multisystem features, but without adrenal insufficiency. Endocrinopathies might be overlooked or develop gradually, and may be underreported. As clinical features including FGR, severe infections, anemia and lung problems can be non-specific and are often seen in neonatal medicine, SAMD9-associated conditions may be underdiagnosed. Reaching a specific diagnosis of MIRAGE syndrome is critical for personalized management.